2016
DOI: 10.1186/s12933-016-0376-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between socioeconomic status and metabolic control and diabetes complications: a cross-sectional nationwide study in Chinese adults with type 2 diabetes mellitus

Abstract: BackgroundLow socioeconomic status (SES) is associated with adverse cardiovascular risk factor patterns and poor outcomes in patients with diabetes. The aim of this study was to determine whether SES is associated with the control of blood glucose, blood pressure, blood cholesterol (3Bs), and diabetic complications in Chinese adults with type 2 diabetes.MethodsData regarding patients’ demographics, social economics, diabetes complications, and cardiovascular risk profiles were analyzed for 25,454 patients. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
54
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 24 publications
(23 reference statements)
6
54
2
3
Order By: Relevance
“…Individuals of lower SES have limited income, poorer occupational opportunity, and reduced access to health care services and information. The patients with the lowest household income have been shown to have the highest prevalence of retinopathy and neuropathy 15. However, in the present study, we did not find a significant association between income level and retinopathy level.…”
Section: Discussioncontrasting
confidence: 95%
“…Individuals of lower SES have limited income, poorer occupational opportunity, and reduced access to health care services and information. The patients with the lowest household income have been shown to have the highest prevalence of retinopathy and neuropathy 15. However, in the present study, we did not find a significant association between income level and retinopathy level.…”
Section: Discussioncontrasting
confidence: 95%
“…Increasing risk of DR among patients who were diagnosed with T1DM at older ages has also been reported previously and postulated to be related to increased risk associated with puberty. 32 We also found that youth with T2DM from households with higher net worth had decreased development of DR, similar to previous literature on socioeconomic risk factors for DR which reported that persons of lower affluence levels were at greater risk for DR both for adults 33 and youth 34 with T2DM and T1DM. 35 This may be related to lifestyle factors such as diet, exercise, and smoking.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the PD treatment recommendations do not represent an object of interest in Croatian guidelines for type 2 diabetes mellitus treatment. As all of the countries that participated in this survey belong to low‐ or middle‐income European countries, a type 2 diabetes mellitus prevention strategy would decrease the economic burden of the treatment of type 2 diabetes mellitus complications.…”
Section: Discussionmentioning
confidence: 99%